GOOD FAITH AS A BASIS FOR CONSUMER LIABILITY IN CASH ON DELIVERY (COD) TRANSACTIONS - Admiral Admiral; Puti Mayang Seruni; Surizki Febrianto (Faculty of Law, Universitas Pekalongan, 2023)
Cash on Delivery (COD) is a popular type of transaction in online buying and selling. However, the implementation of the COD feature creates the issue of consumers being reluctant to make payments after the goods have come as agreed. This unilateral cancellation may result in losses for the seller, the application, and the courier. The aim of this research is to examine the legal liabilities of consumers who make unilateral cancellations to prevent losses. This is normative research that employs secondary data from primary, secondary, and tertiary legal materials. The gathered data is then qualitatively analyzed and related with the core problem. According to the findings, the agreement must be made in good faith, which can be defined as subjective good faith (honesty) and objective good faith (propriety and justice) under Article 1338 paragraph 3 of the Civil Code. Judges have the right to evaluate an agreement and terminate it if it contains improper or unfair details. Before the transaction, where the seller and buyer must be honest, good faith plays a significant part in online transactions using the COD method. Buyers are expected to carefully study the description of the items to be purchased because placing an order indicates that the buyer has agreed to the specifications of the goods and will pay when the goods are received. The COD payment method does not allow customers to cancel unilaterally without providing clear reasons and is therefore considered a default